Treatment of Molluscum Contagiosum with 10% Potassium Hydroxide Solution - Atiya Rahman ,Aisha Akhtar ,Saadia Tabassum ,Rana Shakil Ahmad (Journal of Rawalpindi Medical College, 2017)
Background: To determine the efficacy and safety of topical 10% potassium hydroxide solution in the treatment of molluscum contagiosum (MC) . Methods: An open, prospective, non-randomized study of one year duration was conducted using 10% KOH solution to treat MC. Twenty eight patients completed the study. A total of seven appointments were planned; one baseline and six follow-up visits. 10% KOH was applied to molluscum lesions daily till the lesions resolved or till 3 months had elapsed. Results: Twenty eight patients, among which 22 were children, completed the study. The mean age of patients was 10.6 years. The total lesion count in the patients varied from 5 – 94, with the mean lesion count of 22.14 SD +_ 18.32. There was complete resolution of lesions in 20 (71.4%) of patients , 4 (14.3) had a near complete, 2 (7.1%) had partial and 2 (7.1%) patients had no improvement. 82% patients tolerated the treatment well with no side effects. Conclusion:10% KOH solution is an effective and well tolerated treatment for MC. It is less painful and cost-effective as compared to many well-established therapeutic modalities. It has the advantage of ease of application at home making it an acceptable and feasible option for the treatment of MC.